The molecular basis for the neofunctionalization of the juvenile hormone esterase duplication in Drosophila. (March 2019) - Hopkins, Davis H.; Rane, Rahul V.; Younus, Faisal; Coppin, Chris W.; Pandey, Gunjan; Jackson, Colin J.; Oakeshott, John G.
Abstract: The Drosophila melanogaster enzymes juvenile hormone esterase (DmJHE) and its duplicate, DmJHEdup, present ideal examples for studying the structural changes involved in the neofunctionalization of enzyme duplicates. DmJHE is a hormone esterase with precise regulation and highly specific activity for its substrate, juvenile hormone. DmJHEdup is an odorant degrading esterase (ODE) responsible for processing various kairomones in antennae. Our phylogenetic analysis shows that the JHE lineage predates the hemi/holometabolan split and that several duplications of JHEs have been templates for the evolution of secreted β-esterases such as ODEs through the course of insect evolution. Our biochemical comparisons further show that DmJHE has sufficient substrate promiscuity and activity against odorant esters for a duplicate to evolve a general ODE function against a range of mid-long chain food esters, as is shown in DmJHEdup. This substrate range complements that of the only other general ODE known in this species, Esterase 6. Homology models of DmJHE and DmJHEdup enabled comparisons between each enzyme and the known structures of a lepidopteran JHE and Esterase 6. Both JHEs showed very similar active sites despite low sequence identity (30%). Both ODEs differed drastically from the JHEs and each other, explaining their complementary substrate ranges. A small number of amino acid changes are identified that may have been involved in the early stages of the neofunctionalization of DmJHEdup. Our results provide key insights into the process of neofunctionalization and the structural changes that can be involved. Graphical abstract: Image 1 Highlights: DmJHE has greater promiscuity with food esters than previously thought, providing a basis for neofunctionalization. Key structural features are conserved in insect JHEs in spite of low sequence identity. DmJHEdup has a complementary substrate range with the only other general odorant degrading esterase, DmEST6.